An Analysis Of Post-Traumatic Stress Disorder (PTSD) OF Main Character In “A Private War” Film - Ayu Kartika Septiana; Mawa I Wayan; Prastikayanti Komang Sri (FAKULTAS PENDIDIKAN BAHASA DAN SENI IKIP SARASWATI, 2022)
The purpose of this study is to analyze the gestures and speech shown by the main character of the film who have mental disorders, especially post-traumatic stress disorder. In the analysis, the researcher took